Effects of parenting styles on adolescent and adult adjustment: which parenting style is more beneficial in Spanish families? - Jacome-Mora, Ana; Garcia, Oscar F.; Ertema, Merjema; García, Fernando (Anales de Psicología / Annals of Psychology, 2025)
A classical debate in parenting research is whether one of the two components of parental socialization (strictness and warmth) has a greater impact in psychosocial adjustment not only in early experiences such as in adolescence, but also in the long-term in further developmental stages of the lifecycle. The objective of the present research was to analyze the association between parenting styles and the pattern of psychosocial adjustment in adolescent and adult children. Participants were 2087 Spanish children (58.8% women). A MANOVA (4 × 2 × 4) was applied, where parenting styles, sex, and age groups were independent variables, and social self-concept, self-esteem, emotional unresponsiveness, empathy, and the value of benevolence were dependent variables. The results reveal that children raised in authoritative and indulgent (i.e., warm) families scored better in psychosocial adjustment than other family styles. Empathy scores were higher in warm parenting styles (i.e., authoritative and indulgent), independently of the strictness dimension. Contrary to classical findings with European-American families, parental warmth is positively associated with psychosocial adjustment independently of strictness (i.e., indulgent and authoritative parenting).